The Relationship between Foreign Banking and Credit Access: Panel Analysis Method - Nuri Baltaci; Gizem Akbulut; Gürsan Civelek (Journal of Economics and Political Economy, 2014)
After 1990, the crises in planned economies has resulted with accept of the free market system and disintegration of this country blocks. The transition economies are defined as process of approaching work to the free market system of markets. Privatization efforts especially in finance markets of transition economies have increased interest to these markets of foreign banks. From the studies concern with enter of foreign banks to the market show that there are both advantages and disadvantages. In this study, the relationship between the allocation of credit and the presence of foreign banks in transition economies examined for the period of 1995-2010. In the study panel data method is used. The aim of the study is examine aspects and effects between the presence of the foreign banks and the loans to the private sector. Also the effect of foreign bank on accessing to credit in transition economies examined in macroeconomic level. Findings obtained from the study empirical applications and theoretical supports from literature supports that when the existence share of foreign banks numerically and in the banking sector is examined, it is observed that foreign banks make the credit accessibility of the firms more difficult.
Keywords: P20; E51; G21; 330; Transition economies; Access to credit; Foreign banking